Kaat koort: Study protocol for a pragmatic randomized controlled trial of a multifactorial, multidisciplinary Aboriginal Health Practitioner-led Aboriginal dementia prevention intervention - Carrington CJ. Shepherd; Melissa A. Dunham; Lina Gubhaju; Karen E. Lamb; Digsu N. Koye; Phoebe Fitzpatrick; Emily Banks; Kaarin J. Anstey; Melinda Carrington; Daniel McAullay; Ofra Kalter-Leibovici; Grace Joshy; et al. (Contemporary Clinical Trials Communications)
Background: Limited available data indicate that dementia prevalence rates among Aboriginal and Torres Strait Islander (hereafter Aboriginal) peoples are 3–5 times higher than the overall Australian population. Effective, pragmatic and scalable interventions are urgently required to address this disproportionate burden of dementia in Aboriginal populations. Methods: Kaat Koort is a pragmatic two-arm parallel-group randomized controlled trial which will recruit a sample of 354 participants from two Aboriginal community-controlled health services in the south-west of Western Australia. Eligible participants are aged 35–60 years with risk factors for cardiovascular disease. Participants will be randomized in a 1:1 ratio to receive either a 12-month multifactorial lifestyle intervention (guided by Aboriginal Health Practitioners) that involves cardiovascular risk management, a lifestyle program targeting diet and physical activity, and support for smoking cessation and depression, or usual care (control). The primary endpoints are change in (i) systolic, and (ii) diastolic blood pressure. Secondary endpoints are changes in other cardiovascular risk factors (elevated blood pressure, HDL cholesterol, HbA1c, waist circumference, and absolute cardiovascular risk score), cognitive functioning, and adherence to Australian dietary and physical activity guidelines. Outcomes will be collected at baseline, and 6- and 12-months post-baseline. Discussion: This trial aims to determine the efficacy of a multifactorial lifestyle intervention in reducing blood pressure among Aboriginal people aged 35–60 years at risk of dementia. Trial registration number: ACTRN12621001022853; Australian New Zealand Clinical Trial Registry identifier.